Peculiarities of secret investigative (detective) actions during the pre-trial investigation of criminal misdemeanors - Ya. Yu. Koniushenko; V. V. Ablamska (Bulletin of Kharkiv National University of Internal Affairs)
The purpose of the article is to highlight the theoretical and practical issues regarding the specifics of secret investigative (search) actions during the pre-trial investigation of criminal misdemeanors. Taking into account the purpose goal, the following tasks are to be solved: firstly, to identify and characterize the legal basis for conducting secret investigative (research) actions during the pre-trial investigation of criminal misdemeanors; secondly, to outline the problematic aspects of conducting secret investigative (research) actions during the pre-trial investigation of criminal misdemeanors; thirdly, to formulate the author’s vision for the elimination of identified legislative inaccuracies and contradictions. On the basis of the current legislation and scientific literature, the peculiarities of conducting undercover investigative (research) actions during the investigation of criminal misdemeanors have been investigated.